Opposition and stability in Jemmy Piran's works: An intertextuality study - Darussalam, Zulfardi (LITERA, 2024)
This study seeks to explain how opposition is portrayed in Jemmy Piran's fiction works entitled Surat Dari Seorang Tawanan, Pertempuran Jarak Dekat, and Pertempuran Kedua and to describe how the characters exhibit consistent characterizations. This article adopts Julia Kristeva's intertextuality, the so-called ideologeme, and McHale's heterotopia zone. Piran's three short stories with their socio-historical themes are the main data sources. Data analysis is carried out by looking at the suprasegmental elements and synchronous relations between the short story and socio-historical readers outside the short story. The results demonstrate that, first, it seems that Piran's three fictions are interconnected, exploring socio-historical phenomena suggested by Kristeva's intertextual concept. The socio-historical elements depicted in the three short stories are closely connected to the struggle for East Timor, specifically the conflict between the Indonesian army and Fretilin during the annexation of East Timor from 1980 to 2002. This opposition between the Indonesian military and Fretilin during the annexation of East Timor from 1980 to 2002 is extended to the narratives of civil war. Secondly, intertextuality refers to the process of emphasizing space within the text structure through the utilization of characters and characterizations borrowed from one text to another. McHale has named it the Retour de Personage. In this case, the primary and peripheral characters exhibit a consistent naming pattern and stable characterizations.